An Ovarian Carcinoid Tumor With Peptide YY-Positive Insular Component: A Case Report and Review of the Literature. (July 2016) - Erdenebaatar, Chimeddulam; Yamaguchi, Munekage; Saito, Fumitaka; Motooka, Chisato; Tashiro, Hironori; Katabuchi, Hidetaka
Abstract : Ovarian carcinoid tumors are uncommon and account for 1% of all carcinoid tumors. The insular type of ovarian carcinoid tumor is common in western countries; in contrast, the strumal and trabecular types seem to be common in Asian countries. Strumal and trabecular types are associated with peptide YY (PYY) production, which may cause constipation. Here, we report the case of a 70-yr-old Japanese woman with chronic constipation who was referred to Kumamoto University Hospital because of a right adnexal mass. Imaging tests suggested that the solid mass might be malignant; therefore, abdominal total hysterectomy, bilateral salpingo-oophorectomy, and omentectomy were performed. A subsequent histopathologic examination confirmed an insular carcinoid tumor with a trabecular component in the right ovary. Both components were positive for PYY but not for serotonin. The patient complained of diarrhea instead of constipation soon after the surgery. Because PYY-positive insular carcinoid tumor in the ovary has not been previously reported, we reviewed 19 reported cases of patients with PYY-positive ovarian carcinoid tumors. The origins, common histologic types and symptoms caused by specific peptides secreted in ovarian carcinoid tumors differ between western and Asian countries.